Gender Based Violence in Georgia : Links among Conflict, Economic Opportunities and Services - World Bank Group (World Bank, Washington, DC, 2017)
This report summarizes research undertaken as part of the World Bank State- and Peace-building Fund (SPF) financed grant, Strengthening Capacity for Prevention and Response to Sexual- and Gender-Based Violence in Georgia (GBV). The goal of the grant is to build knowledge and capacity on prevention and response to GBV in Georgia, with a focus on conflict- and displacement-affected populations, economic opportunity and services. The project is part of the World Bank’s global initiative on conflict and Gender-based Violence (GBV). The Global Initiative, financed by the SPF, includes pilot projects across East Asia and the Pacific, Africa, and South Asia (nearly 10 million total in project financing). The aim of the initiative is to increase understanding regarding the development dimensions of GBV and potential areas of enhanced World Bank and development partner programming. While the global initiative supports operational projects in the other regions, the Georgia pilot, representing the Europe and Central Asia Region (ECA), is unique in its focus on deepening knowledge and promoting capacity building. Research was undertaken in Georgia recognizing the country’s legacy of conflict and displacement challenges as well as recent steps taken by the Government of Georgia on gender action and GBV response. Given conflicts in Abkhazia and South Ossetia regions in the 1990s and 2008, Georgia has many conflict-affected people. This includes between 190,000 and 275,000 IDPs, who have been displaced by conflict and make up almost 6 percent of the population, among the highest relative proportions in the world. Also, people living near former conflict zones in Abkhazia and South Ossetia regions continue to experience periodic insecurity and impacts on their living conditions and livelihoods. The research aims to complement existing initiatives by the Government, international partners and the NGO community on GBV in Georgia and to explore openings for additional progress. Specifically, filling research gaps on the potential links between GBV and conflict and internal displacement, economic opportunity, and services.